Rainfall-driven electron acceptors loss constrain natural attenuation of petroleum hydrocarbons and development of a rainfall-responsive biostimulation strategy - Boyan Lai; Zichen Lin; Han Cui; Chaofan Zhang; Dandan Zhou (Journal of Hazardous Materials, 2026)

A dual conductive network-constructed ionogel sensor for human facial expression and action recognition based on the BDAA/AgNWs composition - Yanfang Guan; Han Wang; Minggang Shen; Zichen Li; Zhaoyang Xia; Tong Jin; Zhenxiang Qi; Xiang Li; Ruimeng Jin; Jian Jin; Zhiyong Duan; Guoyong Ye; et al. (Chemical Engineering Journal, 2026)

Notch1-dependent hippocampal apoptosis is associated with monocrotaline-induced anxiety-like behavior - Lai Baochang; Li Fan; Wang Fei; Yan Xianchun; Wang Zichen; Han Mengzhuan; Zhang Yiman; Kang Mengyang; Liu Bing; Wang Ying; Ma Qiang; Jia Pu; et al. (Toxicology, 2026)

Structural evolution of soy protein amyloid fibrils induced by high-temperature pretreatment - Yilin Wang; Xiaoshuai Wang; Zichen Cao; Tianyi Zhang; Yan Zhang; Cuiping Han; Zejian Xu; Xiaonan Sui (Food Hydrocolloids, 2026)

Dynamic sealing mechanisms of drilling fluid in fractured coalbed methane formations: a coupled CFD-DEM numerical study - Zichen Han; Xianyu Yang; Ni Ren; Jiwei Song; Meng Zhao; Man Xue; Mengjia Liang; Xinmin Yan; Chunzheng Jin; Guosheng Jiang; Jihua Cai (Computers and Geotechnics, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Spatiotemporally-graded BHP/G@met scaffold system enables sequential angiogenesis-osteogenesis coupling for accelerated bone regeneration - Han Zhang; Shuqing Chen; Guodong Zhang; Yongbin Wang; Zichen Cui; Fei Chen; Yukun Du; Guanghui Gu; Tianyu Bai; Changlin Lv; Wenkang Yang; Shiqi Xu; et al. (Chemical Engineering Journal, 2025)

Effects of Cardiac Rehabilitation Combined with Enhanced External Counterpulsation on Heart Rate Variability and Autonomic Nervous Function in Chronic Heart Failure - Yiliang Yan; Zichen Han; Bowen Zhou; Kui Li; Jintao Hu; Sigong Yang; Jun Zhang; Xuemin Hu (Cardiovascular Toxicology, 2025)

Design, synthesis, and evaluation of antitumor activity of quinazoline derivatives containing different terminal segments of basic amine groups - Shihao Wang; Zichen Yang; Dongling Gu; JiaHui Han; Hongjing Chen; Hao Wang; JiaXin Zheng; Hongmin Liu; Yu Ke; Qiurong Zhang (Medicinal Chemistry Research, 2025)

Nitrogen deposition enhances accumulation of microbial and plant-derived carbon in forest soils: a global meta-analysis - Chenying Wang; Xiaoyan Li; Meng Zhang; Zichen Han; Yun Xia; Pingping Lian; Liuming Yang; Kai Yue; Yuexin Fan (Plant and Soil, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Design, synthesis and biological evaluation of novel pyrimidine-phenylsulfonylfuroxan hybrids - Dongling Gu; Shihao Wang; Zichen Yang; Hongjing Chen; Jiahui Han; Lingling Chi; Fuqiang Yu; Hao Wang; Jiaxin Zheng; Peirong Zhao; Hongmin Liu; Yu Ke; et al. (Medicinal Chemistry Research, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dynamic analysis on an asymmetric spatial dumbbell-type model - Weipeng Hu; Bo Tang; Zhengqi Han; Pingwei Deng; Zichen Deng (Advances in Space Research, 2024)

Unique role of sulfonic acid exchange resin on preventing copper and zinc precipitation and enhancing metal removal in electrokinetic remediation - Han Cui; Yuchen Wang; Zichen Lin; Hongfeng Lv; Chongwei Cui (Chemical Engineering Journal, 2024)

From Geoparks to Regional Sustainable Development: Geoheritage Protection and Geotourism Promotion of Geoparks in Hebei Province, China - Yanjie Wang; Xiuming Li; Zichen Han; Jinfang Han; Xiaoxiao Pang; Wenli Song; Qinpeng Wang (Geoheritage, 2023)

Matrix stiffness, endothelial dysfunction and atherosclerosis - Zichen Xu; Yi Chen; Yi Wang; Wenbo Han; Wenfeng Xu; Xiaoling Liao; Tao Zhang; Guixue Wang (Molecular Biology Reports, 2023)

Oridonin attenuates the progression of atherosclerosis by inhibiting NLRP3 and activating Nrf2 in apolipoprotein E-deficient mice - Lei Wang; Xiaoqi Zhao; Jiawen Ding; Yutong Liu; Han Liu; Lei Zheng; Hongting Zhao; Zichen Sun; Kuanyu Li; Jing Cai; Tong Qiao (Inflammopharmacology, 2023)
Oridonin, a well-known traditional Chinese herbal medicinal product isolated from Isodon rubescens (Hemsl.) H.Hara, has many potential properties, including anti-inflammatory and antioxidant activities. However, there is no evidence whether oridonin have a protective effect on atherosclerosis. This study focused on the effects of oridonin on oxidative stress and inflammation generated from atherosclerosis. The therapeutic effect on atherosclerosis was evaluated by intraperitoneal injection of oridonin in a high-fat fed ApoE −/− mouse model. We isolated mouse peritoneal macrophages and detected the effect of oridonin on oxidized low-density lipoprotein-induced lipid deposition. Oil red O staining, Masson's staining, dihydroethidium fluorescence staining, immunohistochemical staining, western blotting analysis, immunofluorescence, enzyme-linked immunosorbent assay and quantitative real-time PCR were used to evaluate the effect on atherosclerosis and explore the mechanisms. Oridonin treatment significantly alleviated the progression of atherosclerosis, reduced macrophage infiltration and stabilized plaques. Oridonin could significantly inhibit inflammation associated with NLRP3 activation. Oridonin significantly reduced oxidative stress by blocking Nrf2 ubiquitination and degradation. We also found that oridonin could prevent the formation of foam cells by increasing lipid efflux protein and reducing lipid uptake protein in macrophages. Oridonin has a protective effect on atherosclerosis in ApoE −/− mice, which may be related to the inhibition of NLRP3 and the stabilization of Nrf2. Therefore, oridonin may be a potential therapeutic agent for atherosclerosis.

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Regulation of Hippo/YAP signaling pathway ameliorates cochlear hair cell injury by regulating ferroptosis - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Xiaoyan Ma; Ting Zhang; Baiya Li; Xudong Ma (Tissue and Cell, 2023)

Exposure of Tibetan pregnant women to antibiotics in China: A biomonitoring-based study - Yuanping Wang; Yue Chen; Yangzong Gesang; Zichen Yang; Yi Wang; Ke Zhao; Minghui Han; Chunxia Li; Luobu Ouzhu; Jiwei Wang; Hexing Wang; Qingwu Jiang (Environmental Pollution, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Regulating tumor cholesterol microenvironment to enhance photoimmunotherapy in oral squamous cell carcinoma - Chuanhui Song; Xinyu Zhang; Zichen Cao; Zheng Wei; Meng Zhou; Yufeng Wang; Shengwei Han; Yu Cai; Wei Han (Chemical Engineering Journal, 2023)

A flight-testing campaign to examine inflight icing characteristics and its effects on the flight performance of an Unmanned-Aerial-Vehicle - Nianhong Han; M.A. Siddique; Zichen Zhang; Linchuan Tian; Haiyang Hu; Hui Hu (Cold Regions Science and Technology, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)